AI-Literacy and Pedagogical Utilization Among Lecturers In Islamic Early Childhood Education Program - Masturin, Masturin; Nadhirin, Nadhirin; Amaroh, Siti (THUFULA, 2026)
The use of Artificial Intelligence (AI) in learning remains pedagogically undirected and requires clear policies. This study aims to explore the use of AI in learning in early childhood Islamic education study programs. Informants in this study were lecturers of early childhood Islamic education (PIAUD) at several State Islamic Universities in Central Java. This study used a descriptive qualitative approach with semi-structured interview data collection. The results indicate that the AI literacy of PIAUD lecturers is homogeneous and functional, primarily as a learning aid and completing academic assignments. Frequently used AI applications include ChatGPT, Canva, and other AI applications relevant to their work. The lecturers perceive AI as an effective and efficient tool for enhancing learning creativity. However, there are concerns about the risk of dependency, so regulations on AI use are required. The results of this study are expected to contribute to academic studies on AI utilization and regulation, given that an AI detector has been produced.